Cochicine-induced polyploidization depends on tubulin polymerization in c-metaphase cells - Caperta, A. (2006)
The microtubule cytoskeleton plays a crucial role in the cell cycle and in mitosis. Colchicine is a microtubule-depolymerizing agent that has long been used to induce chromosome individualization in cells arrested at metaphase and also in the induction of polyploid plants. Although attempts have been made to explain the processes and mechanisms underlying polyploidy induction, the role of the cytoskeleton still remains largely unknown. Through immunodetection of alpha-tubulin, different concentrations (0.5 or 5 mM) of colchicine were found to produce opposite effects in the organization of the cytoskeleton in rye (Secale cereale L.). A low concentration (0.5 mM) induced depolymerization of the microtubular cytoskeleton in all phases of the cell cycle. In contrast, a high concentration (5 mM) was found to induce the polymerization of new tubulin-containing structures in c-metaphase cells. Furthermore, both treatments also showed contrasting effects in the induction of polyploid cells. Flow cytometric analysis and quantitative assessments of nucleolus-organizing regions revealed that only the high-concentration colchicine treatment was effective in the formation of polyploid cells. Our studies indicate that spindle disruption alone is insufficient for the induction of polyploid cells. The absence of any tubulin structures in plants treated with colchicine at the low concentration induced cell anomalies, such as the occurrence of nuclei with irregular shape and/or (additional) micronuclei, 12 h after recovery, pointing to a direct effect on cell viability. In contrast, the almost insignificant level of cell anomalies in the high-concentration treatment suggests that the presence of new tubulin- containing structures allows the reconstitution of 4C nuclei and their progression into the cell cycle.